A comparison of the self-esteem of black and white high school pupils - Morrow, Brian Robert (Rhodes University, Faculty of Humanities, Department of Psychology, 1988)
This study investigated the level of self-esteem of black and white high-school students using the Rosenberg self-esteem scale. One hundred and eighty six subjects were used, 63 of them being white while 118 were black. A validation of the Rosenberg scale for the black sample was attempted using a correlation between the scale score and a rating of the subjects by teachers. The results of the study showed no significant difference between the self-esteem levels, while the validation study failed to confirm the validity of the test for black subjects in South Africa. However, the validation study v/as rejected as inconclusive and the results of the comparison accepted as confirmatory of previous research. An incidental positive finding revealed that white males have higher self-esteem than white females,. The theory and past research of self-esteem comparisons between racial groups is reviewed. The conclusion is reached in this study that the concept of self-esteem has outlasted its usefulness in the field of comparisons between racial groups and research of a qualitative nature .can provide further data for the understanding of differences between racial groups.
Keywords: High school students, Black -- South Africa; High school students, White -- South Africa; Self-esteem in adolescence; Rosenberg self-esteem scale